Role of Antioxidants in the Human Diet and Effects of Food Processing - Hernandez Ernesto M; Kamal-Eldin Afaf (Processing and Nutrition of Fats and Oils, 2013)
Food raw materials are fairly stable in their native forms. However, subjecting food raw materials to processes such as maceration, milling, and cooking breaks the protective botanical structure and subjects them to spoilage inter alias by free‐radical reactions. The presence of antioxidants inhibits the oxidation reactions, extends the shelf life of foods, and sustains their sensory and nutritional value. During food processing, proteins are subjected to oxidative modifications by free radicals and reactive oxygen species (ROS) and subsequent changes in their physico‐chemical, functional, and nutritional properties. Oxidation in meat muscles is affected by the amounts of antioxidants present in the muscle including tocopherols, carnosine, lipoic acid, and so on. Foods, especially those originating from plants, play an important role in human health by providing dietary antioxidants. Accumulative research has emphasized the importance of antioxidants in counteracting the oxidative stress and inflammation in human cells and in the body.